146k views
1 vote
1) Select the statement that correctly describes the solution to the equation 4x-6+X-3 = -29

User Akash KC
by
6.6k points

1 Answer

5 votes

To get the solution of the equation 4x-6+x-3 = -29 you cna follow these steps:

1. combine like terms:

4x-6+x-3 = -29

(4x+x)+(-6-3)= -29

(5x)+(-9)= -29

5x-9= -29

2. add 9 on both sides of the equation:

5x -9+9= -29+9

5x= 9-29

5x= -20

3. Divide both sides of the equation by 5

5x= -20

5x/5 = -20/5

x= -20/5

4. Simplify the fraction:

x= -20/5

x= -4

The solution to the equation is x= -4

User Albttx
by
5.8k points